2020
DOI: 10.1186/s13054-020-03183-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac injury associated with severe disease or ICU admission and death in hospitalized patients with COVID-19: a meta-analysis and systematic review

Abstract: Background: Cardiac injury is now a common complication of coronavirus disease (COVID-19), but it remains unclear whether cardiac injury-related biomarkers can be independent predictors of mortality and severe disease development or intensive care unit (ICU) admission. Methods: Two investigators searched the PubMed, EMBASE, Cochrane Library, MEDLINE, Chinese National Knowledge Infrastructure (CNKI), Wanfang, MedRxiv, and ChinaXiv databases for articles published through March 30, 2020. Retrospective studies as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
2
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 56 publications
4
73
2
8
Order By: Relevance
“…Among 143 patients with COVID-19, 31 (21.7%) who had significantly higher mortality. In cardiac injury group, the median duration from illness onset to death was 17.8 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] days; a figure that is comparable to published data in literature. Shi et al [14] described in a retrospective cohort of patients with COVID-19 that 19.7% had cardiac injury with mortality rate of 51.2% compared with 4.5% in non-cardiac injury group.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Among 143 patients with COVID-19, 31 (21.7%) who had significantly higher mortality. In cardiac injury group, the median duration from illness onset to death was 17.8 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] days; a figure that is comparable to published data in literature. Shi et al [14] described in a retrospective cohort of patients with COVID-19 that 19.7% had cardiac injury with mortality rate of 51.2% compared with 4.5% in non-cardiac injury group.…”
Section: Discussionsupporting
confidence: 64%
“…Cardiac injury is a common condition among COVID-19 hospitalized patients [6] and is associated with an increased risk of in-hospital mortality [7]. A recently published systemic review [8] looked at more than 10 studies from Italy, USA, and China, has highlighted that myocardial injury is not uncommon in setting of COVID-19, and can lead to higher mortality in hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that patients with elevated troponin I levels are at higher risk of severe disease, ICU admission, and death. Furthermore, new-onset arrhythmia, elevated biomarkers including creatinine kinase, creatinine kinase-MB, lactate dehydrogenase (LDH), inflammatory biomarkers including Creactive protein (CRP), and interleukin-6 levels are associated with severe disease [37,39]. Moreover, atrial arrhythmias were more common among COVID-19 patients requiring mechanical ventilation [24].…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Increases in a variety of inflammatory pathways, including bradykinin, interleukin-6, C-reactive protein, and growth differentiation factor 15, have been described in COVID-19. 8,9,[38][39][40][41][42][43][44][45][46][47] Further, heparin has been shown to block SARS-CoV-2 viral spike protein binding in experimental studies. [48][49][50] We postulate that the combination of heparin's known antithrombotic and anti-inflammatory effects, 6,7 in addition to viral infectivity attenuation may, at least in part, explain the observed benefit associated with prophylactic anticoagulation.…”
Section: Comparison With Other Evidencementioning
confidence: 99%